Optimum Conditions of Protease Production from Bacillus licheniformis (B1) and its Applications - Haider Jawad Kadhim; Sanaa Burhan Aldeen (Journal of Madenat Alelem University College, 2014)
Forty isolates of Bacillus spp. were isolated from sixty samples including; soil, water and meat. Ability of these isolates to produce protease was evaluated. Bacillus B1 isolated that isolated from soil showed the highest protease production. it was identified as a strain of Bacillus licheniformis.The optimum culture medium and conditions for protease production were casein-yeast extract medium contained soluble casein (0.5g), yeast extract (0.5g), glucose (1g), KH2PO4 (0.02g), K2HPO4 (0.02g) and MgSO4.7H2O (0.01g), in 100ml distilled water, pH 8.0 and incubated at 37˚C. for 48 h. The crude protease exhibited ability to remove the blood color from cloth within 30 min and gelatin from X-ray film within 120 min.